Bilateral simultaneous partial nephrectomy - M. AlTawil (Вестник урологии, 2024)
Introduction. Partial nephrectomy is the treatment of choice for small renal tumors. There are other indications include tumors in a solitary kidney, multiple and bilateral tumors.Сase presentation. A 67-year-old male presented with left flank pain and lower urinary tract symptoms. Computed tomography for abdominal and pelvis showed bilateral renal masses. After doing the essential laboratory tests and investigations, he underwent bilateral open simultaneous partial nephrectomies. After two days, he was discharged with no complains. Follow-up after three months showed no recurrence and acceptable renal function.Discussion. Partial nephrectomy is increasingly used for the management of renal masses. The preservation of renal function with reduced morbidity and equivalent oncologic outcomes led to a paradigm shift away from radical nephrectomy.Conclusion. Bilateral partial nephrectomy is feasible with both clinical and oncological good results.